Forensic efficiency parameters of the Investigator Argus X-12 kit in women from two Mestizo and seven Amerindian populations from Mexico. (May 2017) - Cortés-Trujillo, I.; Ramos-González, B.; Salas-Salas, O.; Zuñiga-Chiquette, F.; Zetina Hernández, A.; Martínez-Cortés, G.; Ruiz-Hernández, M.; González-Martín, A.; Ferragut, J.F.; Rangel-Villalobos, H.
Highlights: Seven Amerindian groups and two Mestizo (admixed) populations from Mexico were studied. Allele frequencies and forensic parameters of the ArgusX-12 kit were estimated. Hardy-Weinberg equilibrium was observed in practically all loci/populations. Genetic relationships and population structure was evaluated. Historical records and X-linked inheritance pattern support the observed population structure. Abstract: Allele frequency distribution and statistical parameters of forensic efficiency concerning the Investigator Argus X-12 kit (Qiagen, Hilden, Germany) were determined in a total sample of 641 unrelated Mexican females, including two Mestizo–admixed– populations ( n  = 309) and seven Amerindian groups ( n  = 332) from the main regions of the country. Most of the 12 X-STRs were in agreement with Hardy-Weinberg expectations in all nine Mexican populations. The power of discrimination in females (PD) and Median exclusion chance for trios (MECT ) and duos (MECD ) of this genetic system based on X-STRs were >99.99%. Although Mexican populations showed significant pairwise differentiation, a closer relationship was evident between Amerindian groups and nearby Mestizos, in agreement with historical records, previous genetic studies, and X-linked inheritance pattern expectations.